2010
DOI: 10.1007/s11524-010-9455-3
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Coroner-Based Surveillance System for Drug-Related Deaths in Los Angeles County

Abstract: Existing data sources do not provide comprehensive and timely information to adequately monitor drug-related mortality in Los Angeles County. To fill this gap, a surveillance system using coroner data was developed to examine patterns in drugrelated deaths. The coroner provided data on all injury deaths in Los Angeles County. A list of keywords that indicate a death was caused by drug use was developed. The cause of death variables in the coroner data were searched for mentions of one of the keywords; if a key… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 27 publications
(35 reference statements)
0
11
0
Order By: Relevance
“…Other studies have reported concern for underreporting of deaths due to heroin use because the inability to identify 6-AM in a postmortem sample, leads to classification of these deaths as being due to morphine use [ 3 , 7 , 8 ]. These studies suggest that heroin toxicity may be responsible for overestimating the contribution of prescription opiates to accidental deaths in the United States [ 3 , 7 , 8 ]. Other studies have suggested that codeine is also over reported as a cause of unintentional drug overdose deaths for similar reasons [ 9 , 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have reported concern for underreporting of deaths due to heroin use because the inability to identify 6-AM in a postmortem sample, leads to classification of these deaths as being due to morphine use [ 3 , 7 , 8 ]. These studies suggest that heroin toxicity may be responsible for overestimating the contribution of prescription opiates to accidental deaths in the United States [ 3 , 7 , 8 ]. Other studies have suggested that codeine is also over reported as a cause of unintentional drug overdose deaths for similar reasons [ 9 , 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…In Allegheny County, we found that morphine was overreported as a cause of death on death certificates; heroin was most likely responsible for a majority of deaths attributed to morphine. Other jurisdictions suspect that some heroin deaths are misclassified as morphine deaths , but the extent of the problem nationwide is unknown. In Allegheny County, we also found that codeine was most likely overreported as a cause of unintentional drug overdose deaths.…”
Section: Discussionmentioning
confidence: 99%
“…Attributions of drugs as a cause of death by the OCME are not mutually exclusive: an overdose death may be attributed to more than one drug. Medical Examiner systems have shown high sensitivity, specificity and positive predictive value to identify external causes of death (Comstock et al, 2005; Landen et al, 2003; Sternfeld et al, 2010). Data regarding cause of death, circumstances of death, and toxicology were collected from the OCME files by trained abstractors using a standardized protocol and data collection forms.…”
Section: Methodsmentioning
confidence: 99%